2019
DOI: 10.1108/ccsm-02-2019-0031
|View full text |Cite
|
Sign up to set email alerts
|

Promoting perceived insider status of indigenous employees

Abstract: Purpose While companies in developed countries are increasingly turning to indigenous employees, integration measures have met with mixed results. Low integration can lead to breach of the psychological contract, i.e. perceived mutual obligations between employee and employer. The purpose of this paper is to identify how leadership and organizational integration measures can be implemented to promote the perceived insider status (PIS) of indigenous employees, thereby fostering fulfillment of the psychological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 177 publications
(529 reference statements)
0
12
0
Order By: Relevance
“…PIS has been studied as a positive relationship as the outcome variable with PP (Dionne et al, 2002 ), as a mediator with organizational citizenship behavior and found no mediation (Caron et al, 2019 ), as the mediator between living a calling and psychological well-being and resulted in a partial mediation (Kang et al, 2021 ). On the other hand, PIS has been studied as an independent variable on IWB and established a significantly positive relationship (Wang et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…PIS has been studied as a positive relationship as the outcome variable with PP (Dionne et al, 2002 ), as a mediator with organizational citizenship behavior and found no mediation (Caron et al, 2019 ), as the mediator between living a calling and psychological well-being and resulted in a partial mediation (Kang et al, 2021 ). On the other hand, PIS has been studied as an independent variable on IWB and established a significantly positive relationship (Wang et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…In opposition to Haar and Brougham's (2013) findings there was no significant relationship between collectivism and job satisfaction, nor did collectivism show a moderating relationship between workplace cultural wellbeing and job satisfaction (hypotheses six and seven). Both Haar and Brougham (2013) and Caron et al (2019) explain that Indigenous peoples tend to be more collectivistic than individualistic, however much of this data is derived from Indigenous groups outside of the United States. It might be possible that, given the smaller population of Native Americans within the United States (1%; Norris, Vines, & Hoeffel, 2012), they may feel pressure to conform to the dominant individualistic culture, especially when working at jobs that are not related to any tribal nation.…”
Section: Discussionmentioning
confidence: 99%
“…There are a number of specificities related to job satisfaction that are proposed to be more important to Indigenous workers than other workers. For example, work-life balance factors, how much the organization values diversity, and cultural awareness toward the Indigenous employee or group have been highlighted as important specifically to those with Indigenous backgrounds (Caron, Asselin, Beaudoin & Muresanu, 2019). Thus, established models of job satisfaction may not accurately represent Indigenous workers' career values .…”
Section: A Model Of Native American Worker Job Satisfactionmentioning
confidence: 99%
See 2 more Smart Citations